Solid Waste Management Practices in the Informal Sector of Gweru, Zimbabwe - Jerie, Steven; Tevera, Daniel (Hindawi Publishing Corporation, 2016)
This paper contributes to the debate on the role of the informal sector in solid waste management by examining the effectiveness of informal sector solid waste management practices in transforming waste into nonwaste in the city of Gweru in Zimbabwe. The study focused on 589 informal enterprises that were surveys using questionnaire interviews and focus group discussions with key informants. Analysis of solid waste management in the informal sector of Gweru has revealed that large amounts of waste are generated indicating poor material efficiency in the enterprises, especially in food market areas where huge amounts of biodegradable material and vegetable wastes are generated and disposed of haphazardly. Analysis of the key factors that include solid waste generation rates, collection frequencies and transportation, waste minimisation, and reduction practices showed that the current waste management system is unsustainable in the long run. The municipality of Gweru needs to provide more resources for financing, training, and manpower to enable effective provision of an environmentally friendly solid waste management system in the city, including the informal sector.